Urgensi Prinsip Wadiah dan Mudharabah sebagai Instrumen Penghimpunan Dana pada lembaga Perbankan syariah - Nur Salsa Fadillah; Ariyanti; Masyhuri (Journal of Islamic Economic Studies, 2025)
This study aims to analyze the role of the Wadi'ah and Mudharabah principles in fund collection in Islamic banking. This research uses a descriptive qualitative approach with a case study model and literature study. The analysis results show that the implementation of the Wadi'ah and Mudharabah principles can strengthen the trust relationship between the bank and customers, increase public participation in the Islamic banking system, and encourage the creation of innovative products that meet market needs. However, challenges in risk management and the uncertainty of business outcomes under the Mudharabah principle are important aspects that the bank needs to pay attention to. Overall, this study provides insights into the importance of applying Islamic principles in fund collection and their contribution to the development of Islamic banking in Indonesia.